Implementasi Budaya Religius Dalam Pembentukan Karakter Disiplin Peserta Didik Di SMAN 2 Bengkalis - Yanti , Selvi; Sarmila, Sarmila; Nuriyati , Tuty (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
This research investigates how the implementation of religious culturecontributes to the development of students' disciplinary character at SMAN 2Bengkalis. It aims to explore how the application of religious culture influencesthe formation of students' discipline. The research methodology employed isdescriptive qualitative, focusing on the students of iSMAN 2 Bengkalis as theprimary subjects. Data collection techniques included observation, interviews,and documentation, while data analysis involved data reduction, data display,and drawing conclusions. The validity of the data was ensured by comparingthe findings from observations and interviews. The study's findings ievealedthat students can cultivate a disciplinary character through the integration ofreligious culture into their daily lives at school. To foster discipline, SMAN 2Bengkalis students practice various religious rituals, such as exchanginggreetings before classes, engaging in prayers before studying, reciting theQur'an (tadarus), congregational prayers during Dhuhr, and participating incollective acts of charity and group readings of the Yasin every Fridaymorning